Estimation of Volumetric Mass Transfer Coefficient in Bioreactor - Zainab Yaquob Atiya (Al-Khwarizmi College of Engineering – University of Baghdad, 2012)
This study is concentrated to investigate the effects of aeration and stirring speed on the volumetric mass transfer coefficient (KLa). A dynamic technique was used in estimating KLa values in order to achieve the aim of this study.This study was done in 10L bioreactor by using two medias:-1. Dionized water2. Xanthan solution (1 g /L)Moreover, the research covered a comparison between the obtained values of KLa.The Xanthan solution was used because of its higher viscosity in comparison with water. It behaves similarly to the cultivation medium when organisms are cultivated in a bioreactor. Growth of organisms in the reactor leads to a change in the viscosity of the medium which affects the mass transfer.Two variables, the effect of air flow rate (3-20 L/min) and the effect of stirring speed (250-700rpm) on KLa value were studied. Other parameters such as temperature, liquid volume, and stirrer shape and stirrer position were held constant; the results demonstrated an increase in KLa value and mass transfer with increasing stirrer speed. Thus at higher speed, better dispersion of the bubbles was obtained. Therefore, that increased the surface / volume ratio which increased the mass transfer area i.e. KLa value.